Mineral supplementation stimulates the immune system and antioxidant responses of dairy cows and reduces somatic cell counts in milk - Warken A.C.* (2018)
© 2018, Academia Brasileira de Ciencias. All rights reserved.The aim of this study was to evaluate whether the use of subcutaneous mineral supplementation would affect metabolic parameters, immunological response, milk quality and composition of dairy cows in the postpartum period. Twelve pregnant primiparous Holstein cows, were divided into two groups: six animals supplemented with the mineral complex (magnesium, phosphorus, potassium, selenium and copper), and six animals used as controls. Milk samples were collected every two other weeks postpartum up to sixty days of lactation to analyze composition and quality. Blood samples were collected, and the levels of ketone bodies, total proteins, glucose, albumin, and globulin were measured. The catalase and superoxide enzymes, reactive oxygen species, tumor necrosis factor, and interleukins were determined. Animals supplemented with minerals showed lower levels of ketone bodies and somatic cell counts on days 30, 45 and 60 of the experiment, without changes in milk composition compared to the control group. Supplemented cows had lower levels reactive oxygen species and increased superoxide enzymes activity. Total protein, globulin and cytokine levels were higher in cows supplemented with mineral complexes. Therefore, we can conclude that subcutaneous mineral supplementation improved the immune response and minimized the oxidative stress in dairy cows during lactation.